New Results in Numerical and Experimental Fluid Mechanics VIII Contributions to the 17th STAB/DGLR Symposium Berlin, Germany 2010 - Dillmann, Andreas; Heller, Gerd.; Kreplin, Hans-Peter.; Nitsche, Wolfgang; Peltzer, Inken; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This volume contains the contributions to the 17th Symposium of STAB (German Aerospace Aerodynamics Association). STAB includes German scientists and engineers from universities, research establishments and industry doing research and project work in numerical and experimental fluid mechanics and aerodynamics, mainly for aerospace but also for other applications. Many of the contributions collected in this book present results from national and European Community sponsored projects. This volume gives a broad overview of the ongoing work in this field in Germany and spans a wide range of topics: airplane aerodynamics, multidisciplinary optimization and new configurations, hypersonic flows and aerothermodynamics, flow control (drag reduction and laminar flow control), rotorcraft aerodynamics, aeroelasticity and structural dynamics, numerical simulation, experimental simulation and test techniques, aeroacoustics as well as the new fields of biomedical flows, convective flows, aerodynamics and acoustics of high-speed trains.
Airplane Aerodynamics -- Multidisciplinary Optimization and New Configurations -- Hypersonic Flows and Aerothermodynamics -- Flow Control -- Flow Control – Drag Reduction -- Laminar Flow Control and Transition -- Rotorcraft Aerodynamics -- Aeroelasticity and Structural Dynamics -- Numerical Simulation -- Numerical Aerodynamics -- Numerical Simulation of Biomedical and Convective Flows -- Experimental Simulation and Test Techniques -- Aeroacoustics -- Aerodynamics and Acoustics of Trains.
Keywords: Aerospace engineering; Astronautics; Fluids; Fluid mechanics; Aerospace Technology and Astronautics; Fluid- and Aerodynamics; Engineering Fluid Dynamics